Heatwaves and cold snaps have complex effects on the relationship between Daphnia magna and its microsporidian parasite Ordospora colligata - McCartan, Niamh (Trinity College Dublin. School of Natural Sciences. Discipline of Zoology, 2025)
Climate change is resulting in far-reaching impacts on nature, the economy, and society. Yet climate change is not just a mean increase in temperature but can involve an increase in anomalous weather events like heatwaves, cold snaps. Indeed, the frequency and intensity of extreme thermal variation is on the rise globally. Climate change is altering disease outcomes, yet little is known about just how attributes of heatwaves and cold snaps (for example, amplitude or duration) alter the host-pathogen dynamic, particularly in real-world systems. In this thesis, I investigate how a water flea (Daphnia magna) responds to infection with its microsporidian parasite Ordospora colligata, under variable thermal conditions. Over two experiments, 128 unique heatwave and cold snap treatments with varying amplitudes and durations were performed at the individual level across four time points in relation to parasite exposure, while four treatments with the same duration but different amplitudes were performed at the population level. All experiments occurred across an identical, broad range of baseline temperatures (14, 17, 20, and 23°C). My results show that the effects of both cold snaps and heatwaves are highly context-dependent; not all extreme temperature changes produce the same outcome. Indeed, the outcome of parasite fitness can depend on the baseline temperature at which the thermal event is applied, the timing of the thermal event in relation to parasite exposure, and the amplitude and duration of the pulse. Heatwaves and cold snaps have distinct and often contrasting effects: heatwaves tend to reduce parasite fitness at high baseline temperatures, while cold snaps increase fitness. At the population level, heatwaves will have long-lasting effects, while cold snaps will have a short-term, delayed increase in parasite fitness. Finally, parasite fitness can scale from individual to population-level. Overall, this work highlights the complexity of disease outcomes under thermal extremes and underscores the challenges of making ecological predictions in a changing climate. These studies contribute to a growing body of work on anomalous weather and its implications for infectious disease.
APPROVED
Keywords: climate change; extreme temperature; heatwaves; cold snaps; disease; host; parasite; Daphnia magna; Ordospora colligata